Modulating the Levels of Plant Hormone Cytokinins at the Host-Pathogen Interface - Naseem, Muhammad; Shams, Shabana; Roitsch, Thomas (Methods in molecular biology, 2017)
Cytokinins are adenine and non-adenine derived heterogeneous class of regulatory molecules that participate in almost every aspect of plant biology. They also affect plant defense responses as well as help microbial pathogens to establish pathogenesis. The functional approaches that ensure desired and subtle modulations in the levels of plant cytokinins are highly instrumental in assessing their functions in plant immunity. Here, we describe a detailed working protocol regarding the enhanced production of cytokinins from plants that harbor isopentenyltransferase (IPT) enzyme gene under the control of 4xJERE (jasmonic acid and elicitor-responsive element) pathogen-inducible promoter. Our devised expression system is a context-dependent solution when it comes to investigating host-pathogen interactions under the modulated conditions of plant cytokinins.
Keywords: transformace genetická; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Plant Diseases; regulátory růstu rostlin; fenotyp; interakce hostitele a patogenu; nemoci rostlin; Cytokinins; geneticky modifikované rostliny; Plant Immunity; imunita rostlin; Signal Transduction; Transformation, Genetic; cytokininy; Plants, Genetically Modified; Plant Growth Regulators; signální transdukce; Host-Pathogen Interactions; Phenotype